What's in a name?: Digital resources and resistance at the global periphery - Kent, Michael (Chandos Publishing, 2012)
Postcolonial theory was transformative of both the humanities and social sciences after the Second World War. However its power and influence is even more startling and unpredictable when applied to ‘virtual’ geographies and nations. This chapter examines questions of ownership and rights over ‘virtual nations’ via their domain names. The right to own, buy and sell virtual real estate has proved one of the most challenging and fascinating applications of postcolonial theory in the twenty-first century.